THE USE OF MULTIMEDIA INTERACTIVE DEVICE OF EPRESENTER IS IN TEACHING OF MATHEMATICS - Dobroshtan, E. (Journal of Information Technologies in Education (ITE), 2011)
The use of multimedia interactive device of eRresenter is examined in teaching of mathematics as will build on for studies and presentation.